Estudio de factibilidad de la ionización de partículas de CO2 emitidas por automotores a diésel, para su empleo en el desarrollo de filtros electroestáticos - Chiliquinga Toro, Víctor Alfonso (2016)
This paper presents the research on methods of ionization particles of CO2 and technique for collection and separation, whereby the design of a prototype was raised by a specialized design software (AutoCAD), which has features physical and electromagnetic presented in graphs and tables, plus these features are calculated and presented based on similar studies even contain experimental demonstrations.